The Discovery of Buried Archaeological Structures at Saepinum and the Villa of Neratii (Valley of Tammaro River, Italy) Through Data-Adaptive Probability-Based Electrical Resistivity Tomography Using the Tensorial Acquisition Mode - Andrea Capozzi; Marilena Cozzolino; Federica Fasano; Vincenzo Gentile; Paolo Mauriello (Applied Sciences)
The Valley of Tammaro River lies between the regions of Molise and Campania in central southern Italy. The area has been inhabited since ancient times due to its fertile soil and plentiful water resources. The interest in this region is enhanced by the many urban centers and the isolated and rural building complexes that date back to the Samnite era and are connected by a road system that is still in use today. Saepinum, regarded as the symbol of Roman civilization in the Molise area (Italy), is one of these. Before becoming a Roman municipium and then a medieval and contemporary rural community, it was a Samnite trade forum and service center. A suburban villa belonging to the Gens Neratia, a family originally from the Roman municipality of Saepinum, is connected to it approximately 2 km northeast. Both sites were partially excavated, and much more can be learned from the material still available. To this end, geoelectrical studies using the tensor acquisition mode were used to conduct geophysical surveys in certain sectors. The data were processed using Data-Adaptive Probability-Based Electrical Resistivity Tomography, here adapted for the first time to Apparent Resistivity Tensor Analysis. The trace of the apparent resistivity tensor provides distortion-free maps and demonstrates that the anomalies are closely constrained on the source bodies.